The Problem of Interfaith Marriage in Indonesia: A Juridical-Normative Approach - Eka Aditya, Mochammad Rizky; Khoirunnisa, Dinda; Fawwas, Fawwas; Qiston, Ajid; Azizah, Aisyah Zarah (El-Usrah: Jurnal Hukum Keluarga, 2023)
Interfaith marriage is a marriage between the bride and groom of different religions and beliefs which is a problem in Islamic law in Indonesia. The regulation regarding the prohibition of interfaith marriage is affirmed in Article 2 paragraph (1) of Law Number 1 of 1974 concerning Marriage. The focus of this study is to analyze the Indonesian legal rules regarding interfaith marriage that are increasingly emerging in Indonesia. The research method uses normative juridical legal methods, data collection techniques namely by analyzing articles, books and references related to the discussion. The results showed that interfaith marriage is not justified in Indonesian legislation with the argument that interfaith marriage is contrary to the religious teachings of Indonesian citizens and can eliminate the basic rights of marriage for husbands, wives and children. As a result of the ban on interfaith marriage, Indonesian citizens are guaranteed legal protection during marriage and after divorce.